기억을 주제로 한 현대 도자작품 연구 - 이규혁; Lee Kyu Hyuk (기초조형학연구, 2019)
기억(Memory)이란 이전의 인상이나 경험을 의식 속에 간직하거나 다시 생각해내는 것을 말한다. 기억은 사회라는 공동생활을 영위하는 집단에서 발생하며 규칙과 규범, 시간과 공간에 대한 이해, 언어와 같은 커뮤니케이션 수단 등이 전제된다. 사회 구성원으로서 개인의 기억과 그에 따른 행동은 개인들의 상호 결합에서 나타나는 결과이다. 과거에 대한 의미 부여의 과정은 항상 재현(representation)이라는 특정한 사회적 실천 작용을 수반한다. 재현의 과정을 통해 과거의 상처에서 벗어나기도 하고 현재를 수정하며 미래를 준비하기도 한다. 재현의 관점에서 기억에 대한 질문들은 과거에 대한 특별한 내용과 형식으로서 그 사회적 기능과 효과가 무엇인가를 고려해야 한다. 내용으로서 기억에 대한 문제는 구체적인 과거의 인물, 사건, 장소와 시간 등은 무엇인가에 대한 동의로부터 시작한다. 형식으로서 기억에 대한 문제는 언어로 된 텍스트뿐만 아니라 다양한 영상 매체, 공간, 건축물, 회화, 조각, 공예, 음악 등 여러 가지 문화적 형식에 대한 논의를 동반한다. 이러한 맥락에서 본 연구는 기억을 주제로 하는 도자작품에 대해 논한다. 과거의 기억을 주제로 작업한 작가 그레이슨 페리(Grayson Perry), 신시아 콘센티노(Cynthia Consentino), 쥬디 마닐러스(Judy Moonelis)의 작품들을 살펴본다. 그레이슨 페리는 어린 시절 학대의 트라우마를 또 다른 자아 ‘클레어’를 통해 극복한다. 신시아 콘센티노는 50년대의 민속예술에서 영감을 받아 재현하는 피규어를 통해 상징과 역사를 탐구한다. 쥬디 마닐러스는 조부모가 살았던 집을 작업장소로 고집하고 그곳에서 제작한 작품을 통해 공유된 기억을 암시한다. 이들의 기억에서 출발한 작품들은 재현과정에서 작가에게 치유를 선물하며 재현으로 완성된 작품은 관람객에게 공감과 위안을 준다. Memory refers to the keeping or recalling of a previous impression or experience in a state consciousness. Memory arises from a group of people who share similar beliefs and interests called society. Society not only determines and sets the rules and what is considered the "norm" but establishes ideas on the understanding of time and space, and the different ways of communication such as language. In terms of individuals in the society, it can be said that the individual's memory and actions are influenced by the overall knowledge/ideas shared by the society. The process of giving meaning to the past always involves a specific social action called representation. Through the process of representation, they can escape wounds from the past, modify the present, and prepare for the future. Questions about memory from the point of view of representation should consider what its social function and effect are as a special content and form of the past. In terms of representation, questions about memory must consider what their social functions and effects are as a particular content and form of the past. The question of memory as a content begins with the consent of what are the specific past figures, events, places and times. The question of memory as a form is accompanied not only by text in the language, but also by discussions on various cultural forms, including various image media, space, buildings, paintings, sculptures, crafts and music. Let's take a look at the works of Grayson Perry, Cynthia Consentino and Judy Moonelis who worked on past memories. During the process of representation, the works which started off from their memories give a gift of healing to the writer, and the works completed in the representation give the viewer sympathy and comfort.